REVITALIZATION OF DRUPADI’S FEMINISM IN THE NOVEL OF DRUPADI PEREMPUAN POLIANDRIS BY SENA GUMIRA AJIDARMA - Wiyatmi Wiyatmi; Afendi Widayat; Andrian Eka Saputra (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2019)
Drupadi is one of the female characters who have important roles and positions in the epic Mahabharata or wayang purwa in Java. In the Indian version Drupadi married five Pandavas. However, in the Javanese version she was only married to Yudhisthira. This paper discuss Drupadi Perempuan Poliandris novel as one of the works which is the reception and transformation of Mahabharata version of India and Java, as a form of reception and transformation of Mahabharata version of India and Java, its existence is considered as a form of revitalization of the classic literary works, especially the character Drupadi using the perspective of feminist literary criticism. The results show that the Drupadi character depicted in the novel tends to return the identity of Drupadi in the Mahabharata of India as the wife of Pandawas after they won the competition held by King Drupada. This is in contrast to Drupadi in the Javanese wayang story depicting Drupadi as the wife Yudhisthira as the oldest Pandawa. In this  novel Drupadi figure is also described as a woman who not only has perfect beauty, but also very critical of her destiny that must be lived.